1991
DOI: 10.1038/bjc.1991.129
|View full text |Cite
|
Sign up to set email alerts
|

Raynaud's phenomenon after combination chemotherapy of testicular cancer, measured by laser Doppler flowmetry. A pilot study

Abstract: Summary The pathophysiology of Raynaud's phenomenon after Cisplatin-Bleomycin-Vinblastine combination chemotherapy, its relationship to polyneuropathy, and response to transcutaneous nerve stimulation (TNS), was studied in eight patients previously treated for testicular cancer. Peripheral circulation in the index finger was measured by laser Doppler flowmetry before and after cold provocation. In all patients there was an exaggerated and prolonged vasoconstrictor response to cold, with a mean flux reduction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Some studies showed an exaggerated response to cold not only in patients with RP but also in patients without finger symptoms before testicular chemotherapy [74,98]. An increased central sympathetic vasoconstrictor reflex and an impaired non-neurogenic vasomuscular, auto-regulation was highlighted in patients suffering from RP syndrome after chemotherapy when compared with the control group (patients without RP after chemotherapy) [99].…”
Section: Drugs Enhancing Vasoconstrictionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies showed an exaggerated response to cold not only in patients with RP but also in patients without finger symptoms before testicular chemotherapy [74,98]. An increased central sympathetic vasoconstrictor reflex and an impaired non-neurogenic vasomuscular, auto-regulation was highlighted in patients suffering from RP syndrome after chemotherapy when compared with the control group (patients without RP after chemotherapy) [99].…”
Section: Drugs Enhancing Vasoconstrictionmentioning
confidence: 99%
“…A study in 1995 that included 90 patients treated with cisplatin-based chemotherapy for more than 1 year after testicular cancer found that 37% of them had developed RP after four cycles of chemotherapy combining cisplatin, bleomycin and vinblastine [73]. RP typically appeared 3 to 6 months after the start of chemotherapy and often persisted for several years [74]. The risk factors identified for the development of RP were high cumulative doses of bleomycin and a combination of bleomycin with vinblastine rather than etoposide.…”
Section: Endothelium Damage And/or Neurotoxicitymentioning
confidence: 99%
“…The clinical features of Raynaud's phenomenon include bilateral or unilateral digital ischemia on cold exposure. Whereas Vogel zang et al [3] found trophic changes of the fingertips in some patients, no trophic skin changes were observed by other in vestigators [11,15]. Digital ischemia led to life-style alterations in 12 of 20 patients of the above-mentioned report [3], Gangrene of the fingers or deterioration with time were not reported.…”
Section: Raynaud' S Phenomenonmentioning
confidence: 87%
“…Since bleomycin is known to cause structural alterations in the small blood ves sels, a minor contribution of anatomical changes cannot be excluded. In a study using laser Doppler flowmetry [15] an exaggerated and prolonged vasoconstrictor response to cold, with a mean flux reduction of 61%, was found. Moreover, the mean restitution time exceeded 7 min.…”
Section: Raynaud' S Phenomenonmentioning
confidence: 99%
“…However, it has been shown that disturbed innervations of blood vessels in ª 2006 European Society for Medical Oncology the legs and disturbed perceptions of temperature are longterm complications after RPLND in TCSs [17].…”
Section: Secondary Malignancymentioning
confidence: 99%